Interface selective vector magnetometry of FeNi/Cu/Co trilayer spin-valve structures - Bland, J; Daboo, C; Patel, M; Fujimoto, T; Penfold, J (1998)
Using polarized neutron reflectometry (PNR) together with superconducting quantum interference device magnetometry, the interface and interior magnetic moments have been determined for each of the ultrathin FeNi and Co layers within an epitaxial FeNi/Cu/Co trilayer structure, so demonstrating interface selectivity in layers of the same nominal chemical composition. The reduced moment found for the Co/Cu and FeNi/Cu interface regions are consistent with a model of enhanced electron spin-flip scattering at rough interfaces proposed to explain the temperature dependence of the giant magnetoresistance amplitude in FeNi/Cu/Co spin-valve structures. We further show that the layer-dependent vector moments can be determined by PNR with high precision.